Mannose-6-phosphate regulates destruction of lipid-linked oligosaccharides - Gao, Ningguo (The American Society for Cell Biology, 2011)
Mannose-6-phosphate (M6P) is an essential precursor for mannosyl glycoconjugates, including lipid-linked oligosaccharides (LLO; glucose(3)mannose(9)GlcNAc(2)-P-P-dolichol) used for protein N-glycosylation. In permeabilized mammalian cells, M6P also causes specific LLO cleavage. However, the context and purpose of this paradoxical reaction are unknown. In this study, we used intact mouse embryonic fibroblasts to show that endoplasmic reticulum (ER) stress elevates M6P concentrations, leading to cleavage of the LLO pyrophosphate linkage with recovery of its lipid and lumenal glycan components. We demonstrate that this M6P originates from glycogen, with glycogenolysis activated by the kinase domain of the stress sensor IRE1-α. The apparent futility of M6P causing destruction of its LLO product was resolved by experiments with another stress sensor, PKR-like ER kinase (PERK), which attenuates translation. PERK's reduction of N-glycoprotein synthesis (which consumes LLOs) stabilized steady-state LLO levels despite continuous LLO destruction. However, infection with herpes simplex virus 1, an N-glycoprotein-bearing pathogen that impairs PERK signaling, not only caused LLO destruction but depleted LLO levels as well. In conclusion, the common metabolite M6P is also part of a novel mammalian stress-signaling pathway, responding to viral stress by depleting host LLOs required for N-glycosylation of virus-associated polypeptides. Apparently conserved throughout evolution, LLO destruction may be a response to a variety of environmental stresses.